The Literature of American Library History, 2012–2013 - Goedeken, Edward A. (Information & culture, 2016)
It has been nearly fifty years since the first issue of the Journal of Library History rolled off the press at Florida State University. The journal's inaugural issue appeared in January 1966, and within two years Michael Harris had crafted the first review of historical writings in "The Year's Work in American Library History, 1967." This essay, therefore, follows a hallowed tradition of nearly a half century whereby the writings on American library history are surveyed and commented upon. Each time the survey is published, the author is surprised that despite the relatively small space historical scholarship occupies on the library and information science stage, a remarkable number of books and articles are consistently generated dealing with the broad expanse of topics that concern the discipline. He has maintained the traditional subject rubrics, although this time he added a category called the "History of Information," which reflects the burgeoning literature devoted to that rather amorphous and still developing aspect of our historical pantheon.